Informal vocational training and sustainable livelihood skills among unemployed youth in low-income countries: Insights from a SWOT analysis of tailoring apprenticeships in Cameroon - Ngyah-Etchutambe, Ijang Bih; Aki, Etta Mercy; Mbi, Suzan Ebai; Farinkia, Ndang Gilbert (Frontiers in Education, 2022)
Many low- and middle-income countries have very high levels of youth unemployment. Self-employment provides one path to economic independence for these youths, but to be successful, they require both technical and entrepreneurial skills. Most youth employment interventions and research have focused on the formal education sector, which has limited the understanding of the role of education in reducing youth unemployment. The role of informal learning opportunities offered by small businesses and micro-enterprises, which constitute one of the largest sectors of the economy in many low- and middle-income countries have been undermined. This study examines the potential of such learning opportunities through a case study of informal apprenticeships in tailoring in Cameroon, Central Africa. A Strengths, Weaknesses, Opportunities and Threats analysis drew on the perspectives of both informal trainers (n = 42: 88% women) and apprentices (n = 16; Mean age: 22 years; 69 % women) in small-tailoring enterprises in the city of Buea. Qualitative data from semi-structured interviews were subjected to a thematic analysis. The perceived strengths of informal apprenticeships included developing suitable work strategies, attitudes, technical and entrepreneurial skills in unemployed youth through practice and collaboration with other apprentices. However, participants also identified several weaknesses of informal training, including inadequate access to specialized machines and limitations on training imposed by the poor literacy skills of some apprentices. Most respondents perceived that tailoring provided an opportunity for a lucrative career while meeting their community’s need for appropriate clothing. However, high taxes and constant power failure were identified as threats to the continuing viability of local tailoring. Trainers also noted that few youths were interested in learning the trade. Taken together, the results indicate that the potential for informal vocational training to nurture youths towards developing their own enterprise would be strengthened if training included basic literacy skills, building self-confidence, introducing strategies to raise and manage capital and the production of attractive designs to match their competition.